Foreign direct investment in Kazakhstan: a success story over the years of independence of the republic - Rakhmatullayeva, D.; Khajiyeva, A.; Abduraimov, O. (Farabi Journal of Social Sciences, 2021)
The article analyzes the attraction of foreign direct investment to Kazakhstan since the country gained independence. During the period under review (1991-2020), the authors made a macroeconomic analysis of statistical data on the dynamics of Kazakhstan’s real GDP according to the IMF, with an emphasis on the analysis of the cyclical nature of the national economy. We analyzed in detail the inflows of foreign direct investment to Kazakhstan by volume, by type of economic activity, by types of direct investors according to the databases of UNCTAD and the National Bank of the Republic of Kazakhstan. In addition, we also analyzed the trends in attracting foreign direct investment in the CIS and Central Asia region, based on which we assessed the position of the republic in these regions in terms of attracting foreign direct investment. In addition, we gave a brief overview of the global situation on them, taking into account the pre- and post-pandemic crisis. The authors attempted to assess the effectiveness of government measures to improve the investment attractiveness of Kazakhstan and analyze the prospects for the development of the policy of attracting foreign direct investment to the republic based on the assessments of international experts. In conclusion, we gave the recommendations to improve the policy of attracting foreign investors to Kazakhstan. Keywords: Kazakhstan, independence, foreign direct investment, investment attractiveness